2017
DOI: 10.1111/eci.12776
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNA‐5196 in the pathogenesis of systemic sclerosis

Abstract: These results suggest that microRNA-5196 can be used as a potential biomarker characterising SSc. Overall, this study may open new possibilities for the development of microRNA-5196-based diagnostics and therapy in early phases of SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…2 ). Similar to the previously published results (Ciechomska et al 2017 ), we have also seen increased expression of miRNA-5196 in SSc sera (Fig. 1 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…2 ). Similar to the previously published results (Ciechomska et al 2017 ), we have also seen increased expression of miRNA-5196 in SSc sera (Fig. 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…These molecules play an important role in inflammation and progression of rheumatic diseases (Araki and Mimura 2017 ; Dey et al 2016 ; Magyari et al 2014 ). Indeed, in the previous paper we have shown that miRNA-5196 targets Fra2 and subsequently reduces profibrotic TIMP-1 production in SSc monocytes (Ciechomska et al 2017 ). MiRNA-5196 binds to five seed regions within 3′UTR of Fra2, therefore, can negatively regulate gene expression of target mRNA (Ciechomska et al 2017 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These types of personalized, individualized medicine approaches where miRNA profiling is monitored for each patient to develop a unique picture of progression after therapy may have more value than attention to normalized or population‐based metrics of therapy effectiveness and progression. Notably, the most significantly decreased miRNA in response to AC‐ACT was miR‐5196‐5p, which targets the Fra2 gene, plays a critical role in the progression of human cancers, and it is involved in IL‐4 production for tumor immunity suppressor . Reduction in miR‐5196‐5p by AC‐ACT may suppress cancer progression but also immune potency will be inhibited.…”
Section: Discussionmentioning
confidence: 99%